2012
DOI: 10.1002/app.34699
|View full text |Cite
|
Sign up to set email alerts
|

In situ solvothermal synthesis and characterization of transparent epoxy/TiO2 nanocomposites

Abstract: A solvothermal process was developed to in situ prepare epoxy (EP)/TiO 2 hybrid precursors. The chemical structure of samples was confirmed by X-ray and Fourier transformed infrared spectroscopy. Field emission scanning electron microscope micrographs of cured EP/ TiO 2 hybrid composites showed that well-dispersed TiO 2 nanoparticles were successfully in situ formed in epoxy matrix through the solvothermal process. The thermogravimetic analysis, DSC, and gel content measurements showed that EP/TiO 2 hybrid pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…The observed properties of our nanocomposites were compared to epoxy/TiO 2 and epoxy/CNTs nanocomposites found in literature: some authors found improved T g , thermal stability and/or mechanical properties [39][40][41] while other report on a decrease in T g as well as thermal stability [42]. Multi wall CNT as well as TiO 2 decreased the T g , but the combination of titania and CNT into a hybrid structure reduces the decrease of T g [43].…”
Section: à2mentioning
confidence: 92%
“…The observed properties of our nanocomposites were compared to epoxy/TiO 2 and epoxy/CNTs nanocomposites found in literature: some authors found improved T g , thermal stability and/or mechanical properties [39][40][41] while other report on a decrease in T g as well as thermal stability [42]. Multi wall CNT as well as TiO 2 decreased the T g , but the combination of titania and CNT into a hybrid structure reduces the decrease of T g [43].…”
Section: à2mentioning
confidence: 92%
“…The copolymer sheets with the sample size of 1 % 2 % 0.2 cm were immersed in THF at room temperature for 4 days. The insoluble part was removed from the solvent and dried at 60°C until the weight was constant (W 2 ), after approximately 24 h. The gel content was calculated based on Equation (5) [57,58]: (5) 3. Results and discussion 3.…”
Section: Characterization Of the Aeso-co-pmmamentioning
confidence: 99%
“…They showed that 5.0 wt % TiO 2 nanoparticles were well dispersed in the epoxy matrix and showed better properties on UV absorption. Zhang et al . also showed that TiO 2 nanoparticles improved the UV‐absorption properties in composite coatings.…”
Section: Introductionmentioning
confidence: 99%